2014
DOI: 10.3109/00207454.2014.886204
|View full text |Cite
|
Sign up to set email alerts
|

Towards establishing a multiple sclerosis biobank in Jordan

Abstract: Genome-wide association studies (GWAS) have been a promising approach in unraveling genetic associations to multiple sclerosis (MS), a complex, multifactorial disease. Biobanks are repositories of patient biospecimens and information that can promote GWAS research. However, the success of GWAS and biobanking is dependent on the level of participation of MS patients in genetic research. In order to initiate MS-based biobanking and GWAS research in Jordan, the willingness of MS patients to participate in long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…In a previous population-based study conducted in Jordan, the majority of respondents (75%) favored broad consent and only 4% preferred re-consenting for every study [ 21 ]. This was contrary to the findings of another study that reported that only half of the patients with multiple sclerosis preferred broad consent and 37% would prefer to be re-consented [ 22 ]. It is tempting to argue that the high preference for re-consenting and re-contacting is due to the eagerness to learn of the type of research to be conducted on participants’ biospecimens.…”
Section: Discussioncontrasting
confidence: 97%
“…In a previous population-based study conducted in Jordan, the majority of respondents (75%) favored broad consent and only 4% preferred re-consenting for every study [ 21 ]. This was contrary to the findings of another study that reported that only half of the patients with multiple sclerosis preferred broad consent and 37% would prefer to be re-consented [ 22 ]. It is tempting to argue that the high preference for re-consenting and re-contacting is due to the eagerness to learn of the type of research to be conducted on participants’ biospecimens.…”
Section: Discussioncontrasting
confidence: 97%
“…This may also reflect differences in studies’ designs among different research groups. In Jordan, perspectives toward donating bio-specimens for biobanks were previously reported among multiple sclerosis and dental patients 27,28. Only one study has previously targeted the Jordanian general population 29,30.…”
Section: Discussionmentioning
confidence: 99%
“…9 Many factors were found to be associated with willingness to donate, such as age, gender, education, residence, religion, biobanking knowledge score, family history of disease, trust in the health care system, and history of blood or tissue donation. 2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In addition, willingness to donate varies according to country and culture.…”
Section: Introductionmentioning
confidence: 99%